Diagnostika a lécba benigní subvezikální obstrukce u nezvĕtsené benigní prostatické hyperplazie - Simon, V; Klemenc, J; Votocek, E; Kalvach, J (Rozhledy v chirurgii, 1989)
At the urological department of the First Surgical Clinic, Faculty of general Medicine Charles University in Prague from January 1977 to December 1986 922 men were operated on account of benign obstruction of the cervix. Ninety-one patients, i.e. 9.8%, with some common signs were subjected to clinical analysis. The criterium for inclusion in the group was the finding of a not enlarged, through on palpation frequently altered prostate, the finding of a histological, endoscopic, X-ray and urodynamic examination. The common sign of these patients was the presence of the disease in young age, a prolonged persistence (up to 20 years) and the frequent presence of supravesical congestion, sometimes with a diverticulum of the urinary bladder. The cause of the disease was dyssynergy, urethrovesical hypertrophy of the poesterior commissure, atrophy of the prostate, subtrigonal hyperplasia of the prostate and a secondary contracture. A transurethral operation was performed in 64 patients, a transvesicalar one in 24 and in three a XY plastic operation was made.
Keywords: obstrukce hrdla močového měchýře; Urinary Bladder Neck Obstruction; lidé; Prostate; Prostatic Hyperplasia; Humans; hyperplazie prostaty; Male; mužské pohlaví; Middle Aged; lidé středního věku; prostata